Analysis of the didactic equipment of biology textbooks for lower secondary school - Vácha, Zbyněk; Bohdalová, Markéta (e-Pedagogium, 2021)
The paper deals with the analysis of the didactic equipment of biology textbooks for the lower-secondary school. In total, 35 titles by seven publishing houses were included in the assessment. The method of measuring the didactic equipment of textbooks was used for the survey. This method is based on evaluating the extent of using individual structural parts that fulfil a specific function in the textbook. Therefore, it supports the role of text as a teaching medium. According to the research results, textbooks published by Nová škola, s. r. o. and Fraus appear to be the best.
Keywords: biology textbook; didactic equipment; lower-secondary school.